Perancangan Burner untuk Reaktor Pirolisis Kapasitas 15 kg dengan Bahan Bakar Refuse Derived Fuel (RDF) dan Gas - Muhammad Jamaluddin; Eka Maulana; Eddy Djatmiko (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2022)
This research has several problem formulations, namely how the design stages and what are the main parameters of the burner design for pyrolysis reactors with Refuse Derived Fuel (RDF) and gas fuel. Therefore, the purpose of this research is to produce a burner design for a pyrolysis reactor with Refuse Derived Fuel (RDF) and gas fuel. Burner is a tool that is used to react properly between the fuel and the oxidizing agent, so that the combustion process can occur. The use of a burner can also save fuel used during the combustion process. In this study, the design method used is the Pahl & Beitz method. There are 3 design variants where variant 1 gets a weighting result (2.9), variant 2 (3.7), and variant 3 (3.06). Based on the results of the weighting of the three variants, variant 3 becomes the chosen design which will then be carried out with detailed design and design analysis. From the analysis of the strength of the frame, the safety factor value is while the calorific value needed to burn Low Density Polyethylene (LDPE) plastic in the pyrolysis reactor is 9.3138 kJ/s.